Blue Basin, Trinidad - (:unkn) unknown (Printed in Germany, 2011)
The postcard shows a man standing under the Blue Basin Waterfall in Diego Martin, a town located in the northwest of Trinidad.
Colour: Sepia with hues of grey and brown; Style: Portrait; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Diego Martin; Waterfalls--Trinidad and Tobago; Blue Basin Waterfall (Trinidad and Tobago)